(3efGbH CHj GdYHGS CMeO GdSHJis - (3jhSa Hf jMji Hf YjSi Hf YHO GdQMef GdJGOdj, CHh GdMLGL, GdeYQha HGHf GdnqRnqjGJ,J (B627 (3g` s ((3CHh GdYHGS CMeO (B( (3MejOI (B) (3Hf CHj GdMSf Ydi s)
(3ChdgG (B:s
(3CeG HYO aEfi deG TYQJ ai JCdja UGdMi GdeZQH GdPjf LeYJge ai cJGHi GdehShe H GdJTha Edi QLGd GdJUha s
(3BNQgG (B:s
(3hgPg GdbUI ai GdSjQI UMjMI GfJgi GdJYQja HGdTjN G dUGdM Gdhdi CHj GdYHGS CMeO Hf LYaQ GdNRQLi GdeYQha HGdSHJi hGdMeO ddg ced GdcJGH s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGfis
(3HgG CKQ fbY eGAs
(3HgG fXGe GdJYbjHIs
(3ai GdeYgO fSNJGf CNQjGf HQbe (B2089 (3, (B2090 (3JGQjNs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdJGQjNs